Radiofrequency catheter ablation in infants and children
Background: Diagnosis and treatment of paediatric arrhythmias remain challenging. Antiarrhythmic - drugs beta-blockers, class Ic and class III drugs, were the only treatment available for many years. Radiofrequency catheter ablation (RFCA) was introduced for adult patients in 1981 and has been used for children since 1989. Questions remain regarding the efficacy and safety in paediatrics. Method: A retrospective analysis of patient records, 12 years and younger, at Leuven University Hospital, from January 2011 - July 2015 was performed. Results: From January 2011 - July 2015, 51 ablations were performed in 44 patients ≤12 years of age. Mean age was 7 years (range 3 weeks - 12 years), 11 (21.5%) ≤2 years; mean weight 16.5kg (range 3.4 - 56kg); average screening time 33.5min (SD